Unsteady MHD chemically reactive double‐diffusive Casson fluid past a flat plate in porous medium with heat and mass transfer. Issue 5 (28th March 2019) - Das, M.; Mahanta, G.; Shaw, S.; Parida, S.B.
Abstract: In this paper, an attempt has been made to analyze the effects of various parameters, such as Soret and Dufour effects, chemical reaction, magnetic field, porosity on the fluid flow, and heat and mass transfer of an unsteady Casson fluid flow past a flat plate. Convective boundary conditions in heat and mass transfer and slip constant on velocity have been taken into account for analysis. The governing equations of the model have been solved numerically using the MATLAB program bvp4c. The impact of various parameters of the model on the velocity, temperature, and concentration profiles has been analyzed through different graphs. To get an insight into the physical quantities of engineering interest, viz, skin friction, Sherwood number, and Nusselt number, their numerical values have been computed for various parameters. The range of the parameters used in numerical computations are Pr ⁢ ( 0.3 – 0.8 ), β ( 0.5 – 1.5 ), M ⁢ ( 1 – 5 ), A ( 0.5 – 1.5 ), L 0 ⁢ ( 0.1 – 0.9 ), D f ⁢ ( 0.2 – 4 ), Sr ⁢ ( 0.3 – 6.3 ), and Sc ⁢ ( 0.05 – 0.15 ) . It has been noticed from the tabulated values that the skin friction gets enhanced with the increase in the thermal and solutal Grashof number, whereas its reverse effects have been observed with an increase in the Biot number. In limiting case, the present study is also compared with the available results in the literature.